(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2026)
Hybrid cloud architectures have emerged as one of the most consequential paradigms in contemporary enterprise computing, driven by the dual imperatives of scalability and control. Organizations increasingly seek to integrate on-premises data infrastructures with elastic public cloud resources in order to balance regulatory compliance, cost efficiency, performance, and innovation. Within this evolving technological ecosystem, Amazon Redshift has assumed a critical role as a fully managed, cloud-native data warehouse that enables large-scale analytics, real-time data ingestion, and complex query processing across heterogeneous data environments. The present study develops a theoretically grounded and empirically informed examination of how Amazon Redshift functions within hybrid cloud architectures, focusing on architectural design, workload management, data integration, and performance optimization. The methodological approach of this study is interpretive and design-oriented, relying on comparative literature analysis, architectural modeling through textual reasoning, and critical synthesis of existing research. Instead of empirical experimentation, the article adopts a theory-driven evaluation of how features such as automatic workload management, concurrency scaling, materialized views, and streaming ingestion support hybrid deployment scenarios. The results reveal that Redshift enables a new form of data warehouse elasticity that fundamentally alters how organizations conceptualize capacity planning, performance tuning, and governance across distributed environments. The discussion advances the argument that hybrid cloud data warehousing represents a transitional but durable configuration in the evolution of enterprise analytics. While full cloud migration remains a strategic goal for many organizations, regulatory constraints, legacy investments, and performance considerations ensure that hybrid models will persist. Amazon Redshift, when embedded within a hybrid cloud framework, becomes a socio-technical mediator that aligns technical capabilities with organizational strategy. This study concludes that understanding Redshift in hybrid contexts requires moving beyond product-centric evaluation toward a broader theory of infrastructural integration in the cloud era.